Sequence-encoded quantitative invader assay enables highly sensitive hepatitis B virus DNA quantification in a single tube without the use of a calibration curve. Issue 19 (28th August 2019) - Sheng, Nan; Zou, Bingjie; Tong, Huan; Lu, Yan; Xing, Sixi; Song, Qinxin; Zhou, Guohua
Abstract : Absolute quantification of HBV-DNA by sequence-encoded Quantitative Invader assay in a single tube without using calibration curves. Abstract : Accurately quantifying hepatitis B virus DNA (HBV-DNA) in serum is important in dynamic monitoring and prognosis evaluation for patients with hepatitis B. Routine assays based on real-time polymerase chain reaction (qPCR) for HBV-DNA quantification usually require laborious calibration curves and may bring bias from the biological samples. To enable absolute quantification of HBV-DNA in a single tube, we described a modification of the conventional Q-Invader assay by separately encoding targeted DNA and artificially designed internal quantitative-standard DNA (QS-DNA) at the flaps of the corresponding downstream probes. Quantification of targeted HBV-DNA was readily achieved by the difference in the quantification cycle value (Ct) between itself and QS-DNA. Furthermore, spiked-in QS-DNA before DNA extraction allowed errors caused by DNA extraction to be corrected. Two different gene regions covering eight genotypes were encoded with the same flap to avoid false-negative results. The method demonstrates a high sensitivity, which enables accurate detection of as low as 2 copies of the HBV-DNA plasmid or 20 IU mL −1 HBV-DNA in serum in a single tube. Successful quantification of 50 clinical samples indicates that our method is cost-effective, labor-saving and reproducible, and promising for the ultra-sensitive quantification analysis of many types of pathogens other than HBV.